Strategi Pengembangan Kepemimpinan dan Pengaruhnya terhadap Kemampuan Manajerial Dokter di Rumah Sakit - Een Amalia Pratiwi; Rinawati Rinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze leadership development strategies and their impact on the managerial abilities of doctors in hospitals. This study uses a systematic literature review method with a descriptive qualitative approach, reviewing nationally accredited scientific articles for the period 2021–2025. The results of the study indicate that the implementation of soft skills training, mastery of information technology, strengthening internal communication, and developing organizational culture significantly increase the managerial capacity of doctors. Transformational and situational leadership models have proven effective in encouraging motivation, staff performance, and the quality of hospital services. The challenges of the transition of doctors' roles from clinical to managerial can be overcome through leadership training, mentoring, and blended learning. Thus, a comprehensive, adaptive, and sustainable leadership development strategy is needed to strengthen the managerial abilities of doctors, thereby contributing to increasing the effectiveness of management and the quality of hospital services.